Aplicación de los instrumentos internacionales de derechos humanos y control de convencionalidad (Tema Central) - Añazco Aguilar, Alan Osvaldo (2022)
The effective guarantee of human rights requires a permanent dialogue and construction between the Inter-American Court of Human Rights —hereinafter also the IACHR Court— and the highest courts of constitutional justice. The IACHR Court, in a solvent and extensive manner, has developed the theory of conventionality control, as a way to ensure consistency between domestic legislation and the American Convention on Human Rights —hereinafter also the Convention or ACHR—. This theory complements and must be articulated with the system or models of control of constitutionality provided by each of the countries subscribing to the Convention. In the case of Ecuador, the control of conventionality and the control of constitutionality are intertwined by the principle of direct application of the Constitution and international human rights instruments, a very complex situation, especially when it comes to refrain from applying a rule of legal rank to give way to the direct application of a rule contained in an international human rights instrument.